Selection Analysis of Pre-Employment Card Recipients Using the Simple Additive Weighting (SAW) Method - Tri Ayu Lestari; Harly Okprana; Rizky Khairunnisa Sormin (Yayasan Literasi Sains Indonesia, 2022)
The Pre-Employment Card Program is a work and business capability development program that focuses on job seekers, laborers or workers who have finished their working period, and workers or workers who need to improve their skills, including those who have macro and micro businesses. One of these government programs aims to reduce unemployment due to the economic impact of the Covid-19 virus outbreak. Decision Support System is an effective system used to produce calculations with the output in the form of ranking. And the purpose of this research is to build a decision support system by analyzing the selection of Pre-Recipients of Pre-Employment Cards with the Simple Additive Weighting (SAW) Method. The data source of this study was obtained from the distribution of questionnaires/questionnaires which were distributed randomly to the people of Tempel Village, Kerasaan Rejo Village, Pematang Bandar. This study uses 50 alternatives and 7 criteria.